Perceptions of Pamong Teachers on the Competence of Prospective Teacher in Practice Field Experience (PPL) - Eliwatis, Eliwatis; Sesmiarni, Zulfani; Maimori, Romi; Herawati, Susi; Murni, Yenti (Journal of Islamic Education Students (JIES), 2022)
This study aims to determine the perceptions of tutors regarding the quality of student teacher competency in field experience practice (PPL). The research was limited to PPL students in the study program of Islamic religious education, Arabic language education, English education and mathematics education in the Faculty of Tarbiyah and Teacher Training at UIN Mahmud Yunus Batusangkar. The research method uses a quantitative descriptive approach. The research instrument was a questionnaire with a Likert scale with 70 samples. The results of the study showed that the pedagogical competence of PPL students was in the category of sufficient perception, professional competence was in the good category, personality competence was in the very good category, and social competence was in the good category. The competency of PPL students with very good perceptual quality of tutors is personality competence, while the social and professional competencies of PPL students with good perceptual quality, but for PPL student pedagogical competence it is very important to improve because only perceptual quality is sufficient. These results become input for the person in charge, implementer and manager of PPL at the university.